Genre Fotografi yang Diminati oleh Fotografer di Indonesia - Gunawan, Agnes Paulina (Bina Nusantara University, 2014)
When speaking of progress, photography is one of the things that is experiencing a quite vast development, and relatively wide in terms of technology or its visual feature. What it means by visual feature here is that in a long period of time, a lot has changed in its idea or concept. Also, it means the print media, or even its printing technique. Moreover he most basic of all is its character of the result in the photo itself. Whether the object taken, moment or time of the photo shoot, all these factors quite represent several genres in photography. For example, if the photography is making a human being to become its model, it might mean a modeling photo shoot, kids, or family photo shoot. Also it might mean a studio/indoor photo shoot or an outdoor photo shoot, when speaking of genre category. If the photo taken is a moment or an event, it might be a journalistic genre or a documentation one. Several themes or visual feature in a photo shoot will become one of the aspects for us the subject to be able to categorize the kind of genre they are. Hence, those genres definitely serve different functions.